Developing digital mental health tools for youth with diabetes: an agenda for future research - Babbott, Katie M.; Serlachius, Anna (Frontiers in Clinical Diabetes and Healthcare, 2023)
Youth living with diabetes face a concurrent challenge: managing a chronic health condition and managing the psychosocial and developmental changes that are characteristic of adolescence and young adulthood. Despite these unique challenges, psychological support is often difficult for youth with diabetes to access due to a lack of trained mental health professionals and other resource constraints. Digital wellbeing tools offer the potential to improve access to psychological support for this population. However, very few digital wellbeing tools exist for youth with diabetes. Of those that do exist, very few are evidence based therapies, undermining their contribution to the field. Given the increasing global prevalence of diabetes in young people, the support necessitated by the challenges experienced by this population is not always accessible in a face-to-face setting and cannot be effectively scaled to meet demand. To support the health and wellbeing of youth with diabetes, there is a clear need to develop digital interventions that are widely accessible to users, but, more saliently, grounded in empirical evidence that supports their efficacy. Thus, the purpose of this paper is to offer an agenda for future research, including insights into which psychological techniques and behavioural change theories may be a good conceptual fit for digital mental health interventions, and how these tools may be best developed and utilised by the individuals that need them. Scalable, evidence-based wellbeing tools for this population are urgently required to improve psychological outcomes, and potentially, improve the equity of service access.